2021
DOI: 10.2138/am-2021-7726
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity and thermodynamic functions of partially dehydrated sodium and zinc zeolite A (LTA)

Abstract: This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, over a wide temperature range, it is hard to define the phase of the water and the heat capacity of the water. Recently, Dickson et al reported the heat capacity of water molecules bound to LTA zeolite as 1.09 J/g/K at 320 K by using the difference in heat capacities between dehumidified and wet zeolites . For our estimation of the zeolites studied here, we used the reported heat capacity of adsorbed water molecules on LTA zeolites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, over a wide temperature range, it is hard to define the phase of the water and the heat capacity of the water. Recently, Dickson et al reported the heat capacity of water molecules bound to LTA zeolite as 1.09 J/g/K at 320 K by using the difference in heat capacities between dehumidified and wet zeolites . For our estimation of the zeolites studied here, we used the reported heat capacity of adsorbed water molecules on LTA zeolites.…”
Section: Methodsmentioning
confidence: 99%
“… b CO 2 heat capacity is the averaged value over −20 and 200 °C c Heat capacity of H 2 O was estimated based on the H 2 O molecule adsorbed in LTA zeolite …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation